Successful customer relationship management programs and technologies : issues and trends - Eid, Riyad (Hershey, PA : Business Science Reference, 2012)
'This book offers case studies, methodologies, frameworks and architectures, and generally the cutting edge in research within the field of customer relationship management'--
'Premier reference source'--Cover.
Includes bibliographical references (p. 286-324) and index.
Keywords: Customer relations -- Management -- Data processing; Customer relations -- Management -- Computer programs